2020
DOI: 10.1111/jcmm.15469
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac β‐adrenergic receptor activation mediates distinct and cell type‐dependent changes in the expression and distribution of connexin 43

Abstract: Activation of the sympatho‐β‐adrenergic receptors (β‐ARs) system is a hallmark of heart failure, leading to fibrosis and arrhythmias. Connexin 43 (Cx43) is the most abundant gap junctional protein in the myocardium. Current knowledge is limited regarding Cx43 remodelling in diverse cell types in the diseased myocardium and the underlying mechanism. We studied cell type‐dependent changes in Cx43 remodelling due to β‐AR overactivation and molecular mechanisms involved. Mouse models of isoproterenol stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
0
20
1
Order By: Relevance
“…Protein immunoblotting was performed as previously described 9 , 21 . Protein was extracted from LV tissue by homogenization of tissues with lysis buffer containing phosphatase protease inhibitors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein immunoblotting was performed as previously described 9 , 21 . Protein was extracted from LV tissue by homogenization of tissues with lysis buffer containing phosphatase protease inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…Two independent methods were applied in determination of ROS, as we previously described 21 , 22 . First, O 2- formation was estimated using OCT fresh-frozen LV sections (5 μm) incubated with dihydroethidium (DHE 5 μM, Invitrogen Co.) for 1 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Beta-adrenoceptor stimulation has been shown to result in an up-regulation of Cx43 expression (see Table 2, Salameh et al, 2006 [82,83]. The reduced expression and lateral distribution of Cx43 in cardiomyocytes after β-adrenoceptor stimulation was also shown by others which interestingly was associated with the inverse effects in cardiac fibroblasts (Zhang et al, 2020) [84]. Previously, it was shown that cardiac fibroblasts inhibit β-adrenoceptor-dependent Cx43 signaling in cardiomyocytes involving angiotensin II (Salameh et al, 2013) [85].…”
Section: Gap Junction Remodeling In Atrial Fibrillation (Af)mentioning
confidence: 82%
“…Notably, TGF‐β1 induces an increase of Cx43 that allows the myofibroblasts to couple electrically with the functional tissue‐specific cell type; nonetheless, it might have undesirable consequences. In the cardiac tissue, for instance, where Cx43 is the most abundant isoform of GJs (Zhang et al., 2020), myofibroblasts can cause a substantial TGF‐β1‐dependent depolarization of the cardiomyocytes, as a result of electrotonic cross‐talk that results in a detrimental arrhythmogenic condition (Nagaraju et al., 2019).…”
Section: Discussionmentioning
confidence: 99%